Bacterial attachment to meat surfaces : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University, Palmerston North, New Zealand - Narendran, Valarmathi (Massey University, 2003)
The aim of this study was to optimise the hygienic efficiency of slaughter and dressing operations. Three strategic approaches, namely reducing and removing or killing the bacteria attached to meat surfaces, were considered. The second option of removal was selected for development, as current technology inevitably results in bacterial contamination, while killing bacteria on meat surfaces requires drastic treatments that may adversely affect quality parameters. The initial attachment mechanism between bacteria and the carcass surface (reversible attachment) was studied using the collagen film model system. Bacterial attachment to the collagen model was compared with attachment to cut beef muscle and uncut beef muscle using viable count procedure. Scanning electron microscopy and direct microscopic count procedure using an epifluorescence microscope was also developed using both collagen films mounted on microscope slides and collagen coated microscope slides. The collagen film viable count system was the method selected to model bacterial attachment to meat because of ease and consistency of quantification. There was no positive correlation between attachment and many bacterial cell surface factors such as charge, hydrophobicity, protein and polysaccharide surface molecules. Different eluents were used to identify the principal component interfering with single attachment mechanisms on electrostatic interaction and hydrophobic interaction chromatographic columns and on collagen film. Three components interfering with the isolated attachment mechanisms were identified. They were Tween, sodium chloride (NaCl) and mannose. Further column studies indicated that cell surface proteins play a more important role in cell surface negative charge and hydrophobicity than do surface polysaccharides. A wash solution was formulated using the components Tween, NaCl and mannose to reverse what were believed to be the major attachment mechanisms. Further trials with Tween, NaCl and mannose and increasing their concentrations and the application of increased vigorous rinsing also proved ineffective for washing the cells from meat surfaces. This result also supports the hypothesis that bacterial attachment to meat surface is very complex and multifactorial. Elution studies using 10 % Tri sodium orthophosphate pH 12.0 killed the cells rather than removing them and further work will be directed towards the killing.
Keywords: Meat; Microbiology; Micro-organisms; Adhesion; Food technology; Fields of Research::290000 Engineering and Technology::290100 Industrial Biotechnology and Food Sciences::290103 Food processing